The induction of synaesthesia with chemical agents: a systematic review - Luke, David; Terhune, Devin B. (Frontiers in Psychology, 2013)
Despite the general consensus that synaesthesia emerges at an early developmental stage and is only rarely acquired during adulthood, the transient induction of synaesthesia with chemical agents has been frequently reported in research on different psychoactive substances. Nevertheless, these effects remain poorly understood and have not been systematically incorporated. Here we review the known published studies in which chemical agents were observed to elicit synaesthesia. Across studies there is consistent evidence that serotonin agonists elicit transient experiences of synaesthesia. Despite convergent results across studies, studies investigating the induction of synaesthesia with chemical agents have numerous methodological limitations and little experimental research has been conducted. Cumulatively, these studies implicate the serotonergic system in synaesthesia and have implications for the neurochemical mechanisms underlying this phenomenon but methodological limitations in this research area preclude making firm conclusions regarding whether chemical agents can induce genuine synaesthesia.